2017
DOI: 10.1038/srep41176
|View full text |Cite
|
Sign up to set email alerts
|

Identification of consensus biomarkers for predicting non-genotoxic hepatocarcinogens

Abstract: The assessment of non-genotoxic hepatocarcinogens (NGHCs) is currently relying on two-year rodent bioassays. Toxicogenomics biomarkers provide a potential alternative method for the prioritization of NGHCs that could be useful for risk assessment. However, previous studies using inconsistently classified chemicals as the training set and a single microarray dataset concluded no consensus biomarkers. In this study, 4 consensus biomarkers of A2m, Ca3, Cxcl1, and Cyp8b1 were identified from four large-scale micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…EnrichR is a prominent tool developed in the Ma'ayan lab for inferring knowledge about an input gene set by comparing it to annotated gene sets from over 160 libraries [26]. Decision trees have been extensively applied for the identification of biomarkers [27,28]. Decision trees are transparent and interpretable predictive models but they require considerable programming skills [29].…”
Section: Introductionmentioning
confidence: 99%
“…EnrichR is a prominent tool developed in the Ma'ayan lab for inferring knowledge about an input gene set by comparing it to annotated gene sets from over 160 libraries [26]. Decision trees have been extensively applied for the identification of biomarkers [27,28]. Decision trees are transparent and interpretable predictive models but they require considerable programming skills [29].…”
Section: Introductionmentioning
confidence: 99%
“…F19 achieved a median AUC of 0.809 for all exposure styles; however, its IQR (0.085) and C.V.d (6.47%) were both much higher than the time-invariant biomarker set. Please note that the time-invariant biomarker set further improved the median AUC value by 9% compared to our previously published consensus biomarkers obtained from the 1-day exposure style (median AUC of 0.733) [16]. The results indicated that the time-invariant biomarkers can also be applied to the long-term exposure style and still provide good prediction.…”
Section: Time-invariant Biomarkers and Machine Learning Classifiersmentioning
confidence: 61%
“…Three common exposure styles of the referenced datasets, namely the 1-day, 3-day, and 1-week high-dose exposures, were considered for the identification of the time-invariant biomarkers. First, each consensus biomarker set was identified as the overlapped differential expressed genes (DEGs) based on a t-test (p < 0.05), and a 1.5-fold change [16], which were derived from each common exposure style of these datasets. Subsequently, each consensus biomarker set was cross-checked with the other two exposure styles.…”
Section: Identification Of the Time-invariant Biomarker Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Support vector machines (SVMs) have been shown to yield reliable and efficient classification performances, while limiting overfitting, particularly for cases where the number of features is higher than the number of samples (as often seen with toxicogenomic data). 29 Although a few isolated biomarkers have been used for genotoxicity detection in both environmental and human health applications, such as CYP1A1 and CYP1B1, 38 RAD54, 39 CYP-R, 38 A2m, Ca3, Cxcl1, and Cyp8b1, 40 their correlation with phenotypic genotoxicity endpoints or carcinogenicity has not been quantified. Furthermore, the temporal dependencies of toxicogenomics responses have also not been considered in most cases, since most studies record a snapshot of the responses.…”
Section: Introductionmentioning
confidence: 99%